2021
DOI: 10.3390/biomedicines9091236
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as Regulators and Biomarkers of Cardiovascular Inflammation in the Context of Abdominal Aortic Aneurysms

Abstract: Neutrophils represent up to 70% of circulating leukocytes in healthy humans and combat infection mostly by phagocytosis, degranulation and NETosis. It has been reported that neutrophils are centrally involved in abdominal aortic aneurysm (AAA) pathogenesis. The natural course of AAA is growth and rupture, if left undiagnosed or untreated. The rupture of AAA has a very high mortality and is currently among the leading causes of death worldwide. The use of noninvasive cardiovascular imaging techniques for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 195 publications
0
21
0
Order By: Relevance
“…Neutrophils pose a crucial first line of defense in the innate immune system, as they are the most numerous type of granulocytes (or ‘polymorphonuclear leukocytes’) and can employ several effector mechanisms to eliminate pathogens [ 428 ]. As we have recently reviewed [ 429 , 430 ], neutrophils are recruited to the aneurysm site by various chemotactic factors, such as IL-8, platelet-derived factors or complement components. These mediators are mainly released from the luminal ILT and have been shown to be increased in the blood of AAA patients [ 337 , 393 , 431 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Neutrophils pose a crucial first line of defense in the innate immune system, as they are the most numerous type of granulocytes (or ‘polymorphonuclear leukocytes’) and can employ several effector mechanisms to eliminate pathogens [ 428 ]. As we have recently reviewed [ 429 , 430 ], neutrophils are recruited to the aneurysm site by various chemotactic factors, such as IL-8, platelet-derived factors or complement components. These mediators are mainly released from the luminal ILT and have been shown to be increased in the blood of AAA patients [ 337 , 393 , 431 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…A recent preclinical study revealed that mice are protected from AAA formation by enhancement of membrane-bound ST2-dependant immunosuppressive T-cell expansion [ 21 ]. Summarizing the manifold aspects of aneurysm pathophysiology, AAA is mainly considered a chronic inflammatory disease, where immunological mediators release detrimental constituents and substances at the aneurysm site which contribute to the destruction of the aortic wall [ 6 , 26 ]. However, very little is known about sST2’s origin measured in the circulation, or its expression patterns, mechanisms of release and function in the aorta, particularly in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from EVAR, in the setting of AAA there are known predictors of complications which have been investigated through the years such as serum elastin peptides (SEP) and plasmin–antiplasmin (PAP) complexes, MMP-9, IL-6, C-reactive protein (CRP), antitrypsin and IFN-gamma for AAA size, expansion rate or rupture [ 12 , 13 , 14 , 15 , 16 ]. Circulating, biomechanical, and genetic markers for AAA growth and rupture were reviewed in recent years [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Biomarkers and Compounds In Abdominal Aortic Aneurysms (Untreated Disease)mentioning
confidence: 99%